2014
DOI: 10.1002/2013ja019396
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of large‐amplitude ULF waves through a quasi‐parallel shock at Venus

Abstract: There exist large-amplitude ultralow frequency (ULF) waves in the upstream region of a quasi-parallel shock, which are excited due to the reflected ions by the shock. These waves are then brought back to the shock by the solar wind, and at last they coalesce and merge with the shock. In this paper, with the magnetic field measurements from Venus Express, for the first time we observe the transmission of large-amplitude ULF waves from the upstream region to the downstream under quasi-parallel shock conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
7
29
0
Order By: Relevance
“…In that study, it was shown that the reformation of a quasi-parallel shock can drive strong magnetosheath and magnetospheric wave activity at Mercury. Similar observations have since then also been made at Venus, where Shan et al [2014] observed a transmission of ULF waves from the upstream to the downstream region. Approximately half of the wave events also show pulsations immediately upstream of the shock in a similar frequency span, but at much lower amplitudes, which is also indicative of an upstream source for this wave mode.…”
Section: Large-amplitude Wavessupporting
confidence: 76%
“…In that study, it was shown that the reformation of a quasi-parallel shock can drive strong magnetosheath and magnetospheric wave activity at Mercury. Similar observations have since then also been made at Venus, where Shan et al [2014] observed a transmission of ULF waves from the upstream to the downstream region. Approximately half of the wave events also show pulsations immediately upstream of the shock in a similar frequency span, but at much lower amplitudes, which is also indicative of an upstream source for this wave mode.…”
Section: Large-amplitude Wavessupporting
confidence: 76%
“…Earlier reports revealed the existence of ULF waves upstream of the Venus bow shock [ Russell and Hoppe , ; Orlowski et al ., ; Shan et al ., ]. For the present work, a statistical study of Venusian foreshock ULF wave properties is undertaken using 1 Hz VEX‐MAG data.…”
Section: Discussionmentioning
confidence: 99%
“…Near the Venusian bow shock, Shan et al . [] identified five quasi‐monochromatic ULF wave events originating from the upstream of the quasi‐parallel shock and which seem to have been transmitted downstream. These waves were found to have similar properties in the foreshock and magnetosheath: frequency 0.04–0.05 Hz in spacecraft frame, an average oblique propagation angle of ~32°, left‐handed elliptical polarization, and large amplitude, indicating that the waves are magnetosonic waves, which are blown from upstream to downstream by the solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study compared detailed wave diagnostics in both upstream and downstream regions of the Venusian bow shock and concluded that the downstream waves are transmitted ULF waves. 33 In cases where the steepened fronts are nearly parallel to the quasi-parallel region of the bow shock surface, they can significantly modify the shock structure and the magnetosheath thickness. This is shown in Fig.…”
Section: Transmission Of the Foreshock Turbulencementioning
confidence: 99%